pegegog 2023
DOI: 10.47750/pegegog.13.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Common written error analysis committed by EFL graders. A case study at a secondary school in Vietnam

Abstract: This study investigated common written errors and the causes that language learners frequently commit. A descriptive qualitative approach was conducted with the participation of 57 eleventh-graders at a high school in Hung Yen province during the second term of the academic year 2021-2022. The respondents were requested to participate in five writing tests in three successive months to generate their morphological, lexical, syntactical, and mechanical written errors basing on Ferris' (2014) model of Error Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…With this result, grammar lessons must be reconsidered, whether they should be taught and tested explicitly in individual grammar classes or implicitly in skills classes. That is times when policy makers and curriculum designers, and EFL teachers should reconsider how to help EFL learners apply grammar effectively in their essay writing (Alfaruqy et al, 2022;Do, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…With this result, grammar lessons must be reconsidered, whether they should be taught and tested explicitly in individual grammar classes or implicitly in skills classes. That is times when policy makers and curriculum designers, and EFL teachers should reconsider how to help EFL learners apply grammar effectively in their essay writing (Alfaruqy et al, 2022;Do, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…). Several studies have been conducted to identify the types of errors and the most frequent errors that appeared in the writing of EFL students (Do, 2023;Fatmawati & Harahap, 2023;Lionny & Kusumadewi, 2022;Octaberlina & Muslimin, 2022). The findings indicated that tense and agreement errors are the most common errors.…”
mentioning
confidence: 99%
“…The significance of error analysis in the teaching and learning process cannot be overstated. Teachers can improve suitable instructional resources and effective plans to correct students' errors by understanding their causes (Darus & Subramaniam, 2009;Do, 2023). For students, research on errors can reveal the challenges and barriers they face in their writing (Seitova, 2016;Sompong, 2014).…”
mentioning
confidence: 99%